Preoperative pazopanib in high-risk soft tissue sarcoma: phase II window-of opportunity study of the german interdisciplinary sarcoma group (NOPASS/GISG-04) - Ronellenfitsch, Ulrich; Karampinis, Ioannis; Jakob, Jens; Kasper, Bernd; Nowak, Kai; Pilz, Lothar R.; Attenberger, Ulrike; Gaiser, Timo; Hohenberger, Peter (Annals of surgical oncology, 2019)
BackgroundPreoperative devascularization might improve local control and thus the outcome of patients with soft tissue sarcoma (STS). The multikinase inhibitor pazopanib has antiangiogenic effects and is approved for treating metastatic STS. We conducted a trial of preoperative pazopanib therapy in high-risk STS.MethodsThis single-arm, phase II trial included patients with resectable, non-metastatic, treatment-naïve, high-risk STS. Patients received pazopanib 800 mg daily while waiting for surgery (21-day ‘window of opportunity’). The primary endpoint was metabolic response rate (MRR; proportion of patients with ≥ 50% reduction of mean standardized uptake value [SUVmean] in post- vs. pretreatment fluorodeoxyglucose-positron emission tomography/computed tomography [FDG-PET-CT]). Planned sample size was 35 patients (type I error, 5%; type II error, 20%). A translational substudy explored associations between response and concentration of circulating angiogenic factors.ResultsFutility analysis was performed after 21 patients (11 female, mean age 67 years; liposarcoma n = 15); 17/21 patients were evaluable for the primary endpoint. The MRR was 1/17 (5.9%, 95% confidence interval < 0.01-0.29). Mean change in SUVmean of post- versus pretreatment PET was a 6% decrease (range 65% decrease to 34% increase); 7/21 (33.3%) patients had 12 grade 3/4 toxicities, and 19/21 (95.2%) patients were resected (all R0). One (4.8%) patient suffered a grade 4 postoperative complication (anastomotic leakage). Circulating endothelial progenitor cells, soluble vascular endothelial growth factor, and angiopoietin-2 concentrations showed no relevant changes during treatment.ConclusionsAlthough this study showed that preoperative pazopanib is not effective for unselected high-risk STS patients, relevant treatment effects were observed in a single patient. Future research needs to better define subgroups potentially benefiting from preoperative pazopanib treatment.ClinicalTrials.gov identifierNCT01543802.
Gesehen am 14.05.2019